SELF-ENDORSING VERSUS OTHER-ENDORSING IN VIRTUAL ENVIRONMENTS: The Effect on Brand Attitude and Purchase Intention - Ahn, Sun Joo and Bailenson, Jeremy N. (Journal of Advertising, 2011)
Self-endorsing—the portrayal of potential consumers using products—is a novel advertising strategy made possible by the development of virtual environments. Three experiments compared self-endorsing to endorsing by an unfamiliar other. In Experiment 1, self-endorsing in online advertisements led to higher brand attitude and purchase intention than other-endorsing. Moreover, photographs were a more effective persuasion channel than text. In Experiment 2, participants wore a brand of clothing in a high-immersive virtual environment and preferred the brand worn by their virtual self to the brand worn by others. Experiment 3 demonstrated that an additional mechanism behind self-endorsing was the interactivity of the virtual representation. Evidence for self-referencing as a mediator is presented.
https://katalog.adlr.link/Record/ai-55-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjc1My9KT0EwMDkxLTMzNjc0MDAyMDc